2001
DOI: 10.1021/ef010149b
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Hydrogen Mobility in Functional Groups of Coals Using Tritium Tracer Methods

Abstract: Hydrogen exchange reactions of coal with tritiated water and gaseous hydrogen were investigated to estimate the mobility of hydrogen in coal using not only a batch type reactor but also a flow type reactor. Specifically, the reactivities of functional groups were traced in these reactions. In the reaction of coal with tritiated water at 100°C the hydrogen exchange of functional groups such as hydroxyl group in coals could be estimated. In the pressurized system using stainless batch type reactor aromatic hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…This indicates that the hydrogen bond decreased during the hydrothermal treatment of lignite because of hydrolysis of the oxygen functional group. While water absorbed in KBr may obscure this band, the results agree with Ishihara et al (2002) and Yan et al (2020) and the discussion above.…”
Section: Ftir Analysis Of the Evolution Of Oxygen Functional Groups Dsupporting
confidence: 87%
See 1 more Smart Citation
“…This indicates that the hydrogen bond decreased during the hydrothermal treatment of lignite because of hydrolysis of the oxygen functional group. While water absorbed in KBr may obscure this band, the results agree with Ishihara et al (2002) and Yan et al (2020) and the discussion above.…”
Section: Ftir Analysis Of the Evolution Of Oxygen Functional Groups Dsupporting
confidence: 87%
“…The CH 2 /CH 3 ratio clearly increases in the second stage because hydrolysis of the oxygen functional groups (such as carboxyl, esters, and ethers) plays an important role in this stage. The hydrogen of the functional groups in lignite can exchange with water via electrophilic substitution on addition of water at this temperature (Ishihara et al 1993(Ishihara et al , 2002, and then transfer in lignite or the methyl hydroaromatic structures opposite to the branched aliphatic structures. The H radicals produced by the condensation of free phenol also participate in the hydrogen transfer.…”
Section: Aliphatic Carbon Species (F Almentioning
confidence: 99%
“…[31,32]. The recovery of hydrothermal treatment coal is about 90%, while the ash contents in the treated coal are almost the same with those in the raw coal.…”
Section: Preliminary Evaluation Of the Raw Coal And Hydrothermally Trmentioning
confidence: 89%
“…17,18 However, several researchers reported that catalysts directly promote the transfer of hydrogen from molecular hydrogen to coal rather than through tetralin. 19,20 Li et al 21 revealed that iron-based catalysts mainly promoted coal pyrolysis and the formation of activated hydrogen to accelerate the secondary distribution of H in the reaction. Niu et al 22 reported that iron-based catalysts can directly promote the hydrogen transfer and exchange between coal and the solvent, whereas the α-radical of tetralin acts as an important intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, numerous studies have focused on studying the role of iron-based catalysts in the hydrogenation of coal. For the hydropyrolysis of coal, researchers found that the catalytic activity of iron on cracking was higher than that on hydrogenation, which changes the composition of tar and makes it lighter . In the coal liquefaction process, the conventional theory suggested that iron-based catalysts can split molecular hydrogen into tetralin and then catalyze the fast dehydrogenation of tetralin to release hydrogen for coal hydrogenation. , However, several researchers reported that catalysts directly promote the transfer of hydrogen from molecular hydrogen to coal rather than through tetralin. , Li et al revealed that iron-based catalysts mainly promoted coal pyrolysis and the formation of activated hydrogen to accelerate the secondary distribution of H in the reaction. Niu et al reported that iron-based catalysts can directly promote the hydrogen transfer and exchange between coal and the solvent, whereas the α-radical of tetralin acts as an important intermediate.…”
Section: Introductionmentioning
confidence: 99%